Lepus (Lepus) arcticus Ross 1819 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lepus (Lepus) arcticus Ross 1819 Lepus (Lepus) arcticus Ross 1819, Voy. Discovery, II; ed. 2, App. IV: 170. Type Locality: "Southeast of Cape Bowen" (Nelson, 1909:61) [Possession Bay, Bylot Island, lat. 73E37'N, Canada]. Vernacular Names: Arctic Hare. Subspecies:: Subspecies Lepus (Lepus) arcticus subsp. arcticus Ross 1819 Subspecies Lepus (Lepus) arcticus subsp. bangsii Rhoads 1896 Subspecies Lepus (Lepus) arcticus subsp. groenlandicus Rhoads 1896 Subspecies Lepus (Lepus) arcticus subsp. monstrabilis Nelson 1934 Distribution: Greenland and Canadian arctic islands southward in open tundra to WC shore of Hudson Bay, thence northwest to the west of Fort Anderson on coast of Arctic Ocean. Isolated populations in tundra of N Quebec and Labrador, and on Newfoundland (Canada). Conservation: IUCN – Lower Risk (lc). Discussion: Subgenus Lepus (Averianov, 1998). Formerly included in timidus by Gureev (1964), Angermann (1967), Honacki et al. (1982), and Dixon et al. (1983), but considered distinct by Corbet (1978 c ), Hall (1981), A. J. Baker et al. (1983), and Flux and Angermann (1990). Reviewed by Best and Henry (1994 a , Mammalian Species, 457). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Lagomorpha, pp. 185-211 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 195, DOI: 10.5281/zenodo.7316519